A comparative study for the effect of green roofs in the local climate of Najaf city - Saleem, Younis Mahmood; Abdulrasoul, Ahmed Faik (Iraqi Journal of Architecture and Planning, 2018)
Most Iraqi cities suffer from a stark negligence in achieving equilibrium between the constructed objects and their effects on local climate, especially in providing green areas. This led to disturbing the natural equilibrium in the urban environmental system, which in turn led to an increase in temperature degrees inside the cities, resulting in the cities to move outside of the temporal comfort boundaries. Therefore, this research studies one of the technologies that reduce this temporal effect that was generated by the shortage of green areas in the city, which is the green roofs technology. The green roofs are important technologies that have effects on the local climate, they provide temporal comfort inside the building and outside of it, therefore, they reduce the effect of heat island especially at locations with hot and dry climate, however, the efficiency of the plants in green roofs differs according to the climatic nature and the location specifics. From here, the research problem was assigned about â€œThe lack of a clear picture about the rule that green roofs play in environmental solutions in buildingsâ€, and the object was assigned as â€œCreating a clear and measurable notion about the rule that green roofs play in the climatic aspects for buildings within the urban levelâ€ while the research hypothesis is â€œThe green roofs have a positive rule in improving the environmental performance of buildingsâ€. Keywords: (green roofs, climate, urban heat island, energy preserving)